Luminescence detection of peptide:N-glycanase activity using engineered split inteins. Issue 95 (14th November 2022) - Takahashi, Tsuyoshi; Uchibayashi, Tatsuya; Ishii, Nozomi; Matsuo, Ichiro; Yoshida, Yukiko; Suzuki, Tadashi
Abstract : A convenient method to detect peptide: N -glycanase activity was developed using engineered split inteins in which the N-intein sequences contain N, N ′-diacetylchitobiose. Abstract : A split intein-based method has been developed to detect peptide: N -glycanase (PNGase) activity in live cells. PNGase cleaves the linkage between N, N ′-diacetylchitobiose and the Asn side-chain of N-intein peptides and the products react rapidly with C-intein by protein trans-splicing to generate an active luciferase.